2019
DOI: 10.1111/ele.13324
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use change and the ecological consequences of personality in small mammals

Abstract: Many plants rely on animals for seed dispersal, but are all individuals equally effective at dispersing seeds? If not, then the loss of certain individual dispersers from populations could have cascade effects on ecosystems. Despite the importance of seed dispersal for forest ecosystems, variation among individual dispersers and whether land‐use change interferes with this process remains untested. Through a large‐scale field experiment conducted on small mammal seed dispersers, we show that an individual's pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 57 publications
0
105
1
1
Order By: Relevance
“…Based on these previous findings we speculate that an individual's personality will affect the interaction with novel seeds; in particular, following Brehm et al (2019) we predict that bolder and less anxious individuals will be more likely to interact with novel seeds. Further, Brehm et al (2019) found that landuse change shifts the distribution of personalities within a population, by increasing the proportion of bold, active and anxious individuals and in-turn affecting the potential survival and dispersal of seeds. We thus speculate that small mammal controls on the climate-driven range shift of woody plant species may be also mediated by land-use change effects on the distribution of personalities within a population.…”
Section: Speculationsmentioning
confidence: 63%
See 3 more Smart Citations
“…Based on these previous findings we speculate that an individual's personality will affect the interaction with novel seeds; in particular, following Brehm et al (2019) we predict that bolder and less anxious individuals will be more likely to interact with novel seeds. Further, Brehm et al (2019) found that landuse change shifts the distribution of personalities within a population, by increasing the proportion of bold, active and anxious individuals and in-turn affecting the potential survival and dispersal of seeds. We thus speculate that small mammal controls on the climate-driven range shift of woody plant species may be also mediated by land-use change effects on the distribution of personalities within a population.…”
Section: Speculationsmentioning
confidence: 63%
“…months), allowing for the calculation of indices such as the seed dispersal effectiveness (Schupp et al 2010) and it would also be important to place each species on a predator-mutualist continuum (Zwolak and Crone 2012). Further, we recommend that future seed dispersal studies focusing on 'novel' seeds also consider the critical role played by rodent population density (Lichti et al 2017), the availability of seeds (Xiao et al 2013) as well as the important role of individual-level factors such as personality (Brehm et al 2019).…”
Section: Seed Size Affects Plant Emergencementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, dispersal evolves even in the simplest of systems in response to altered conditions (Hamilton and May 1977;Hargreaves and Eckert 2014), and can be especially important for sessile organisms, such as plants, that have limited opportunities for movement. Seed dispersal, or the movement of offspring away from the source parent plant, provides the opportunity for migration (Zobel et al 2010), facilitating gene flow (Sexton et al 2009), range shifts (Davis and Shaw 2001;Hargreaves et al 2015), and spatial tracking of favorable environmental conditions (Edelaar and Bolnick 2012;Brehm et al 2019) -all which allow for species persistence despite local extirpation (Tilman 1994). Two important drivers of selection on dispersal ability are climate and habitat connectivity or isolation (Mantyka-Pringle et al 2012).…”
Section: Introductionmentioning
confidence: 99%